Human enteric neurons: morphological, electrophysiological, and neurochemical identification. Issue 12 (8th October 2014) - Carbone, S. E.; Jovanovska, V.; Nurgali, K.; Brookes, S. J. H.
Abstract Background Access to tissue, difficulties with dissection, and poor visibility of enteric ganglia have hampered electrophysiological recordings of human enteric neurons. Here, we report a method to combine intracellular recording with simultaneous morphological identification of neurons in the intact myenteric plexus of human colon ex vivo. Methods Specimens of human colon were dissected into flat‐sheet preparations with the myenteric plexus exposed. Myenteric neurons were impaled with conventional microelectrodes containing 5% 5, 6‐carboxyfluorescein in 20 mM Tris buffer and 1 M KCl. Key Results Electrophysiological recordings identified myenteric neurons with S and AH type properties (n = 13, N = 7) which were dye filled and classified during the recording as Dogiel type I (n = 10), Dogiel type II (n = 2), or filamentous (n = 1) cells. This classification was confirmed after fixation, in combination with immunohistochemical characterization. Conclusions & Inferences This method allows electrophysiological characterization with simultaneous identification of morphology. It can be used to identify recorded cells immediately after impalement and greatly facilitates recordings of human myenteric neurons in freshly dissected specimens of tissue. It can also be combined with immunohistochemical labeling of recorded cells.